Wide‐complex tachycardia in a patient with old myocardial infarction. Issue 6 (24th September 2020) - Bhasin, Dinkar; Narang, Rajiv; Parakh, Neeraj
Abstract : An elderly man with a history of coronary artery disease presented with sudden‐onset palpitations. The electrocardiogram showed wide complex tachycardia with left bundle branch morphology which terminated spontaneously. Subsequent ECGs confirmed the diagnosis as atrial fibrillation with aberrant conduction because of a diseased left bundle.